(untitled) (Radiasi : Jurnal Berkala Pendidikan Fisika, 2024)
This study raises the problem of low student learning outcomes in physics subjects, the lack of student activity, and enthusiasm during learning. This Study aims to determine the effect of the Course Review Horay on physics learning outcomes. The population of this study were all students of class XI IPA MAN 4 Aceh Besar consisting of two classes. Sampling was taken using a total sampling technique with 32 students as the experimental class and 36 students as the control class. Data collection was carried out using test instruments, namely pre-test and post-test. The data analysis technique uses the N-Gain test to see the difference in the increase in student learning outcomes in the experimental class and the control class, then the data is analyzed using the t test to see the effect of the course review horay type cooperative learning model on the physics learning outcomes of MAN 4 Aceh Besar students. Based on the results of data analysis, it was obtained that the N-Gain for the experimental class was 0.78, which was included in the high gain index category, while the N-Gain for the control class was 0.69, which was included in the medium gain index category. The results of data analysis using the t-test show that tcount 2.292 > ttable 1.668. Thus it can be concluded that there is an influence of the cooperative learning model type course review horay on the physics learning outcomes of MAN 4 Aceh Besar students (tcount > ttable).